2005
DOI: 10.1016/j.chemosphere.2005.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a novel passive sampler to standard water-column sampling for organic contaminants associated with wastewater effluents entering a New Jersey stream

Abstract: Huckins, J. N.; Furlong, E. T.; Zaugg, S. D.; and Meyer, M. T., "Comparison of a novel passive sampler to standard water-column sampling for organic contaminants associated with wastewater effluents entering a New Jersey stream" (2005 AbstractFour water samples collected using standard depth and width water-column sampling methodology were compared to an innovative passive, in situ, sampler (the polar organic chemical integrative sampler or POCIS) for the detection of 96 organic wastewater-related contaminant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
1
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(114 citation statements)
references
References 22 publications
4
101
1
5
Order By: Relevance
“…These results are in good agreement with previous works indicating a strong retention for some polar herbicides such as atrazine, diazinon, diuron, isoproturon (Alvarez et al, 2004) and simazine (Mazzella et al, 2007). However, the POCIS are frequently deployed for several weeks in the field (Alvarez et al, 2004;Alvarez et al, 2005;Macleod et al, 2007;Matthiessen et al, 2006) and for long exposure times, the desorption phenomena are probably not negligible. In this case we have to investigate the elimination rates in further detail.…”
Section: Desorption Of Det Terbuthylazine and Isoproturon From Pocissupporting
confidence: 81%
See 1 more Smart Citation
“…These results are in good agreement with previous works indicating a strong retention for some polar herbicides such as atrazine, diazinon, diuron, isoproturon (Alvarez et al, 2004) and simazine (Mazzella et al, 2007). However, the POCIS are frequently deployed for several weeks in the field (Alvarez et al, 2004;Alvarez et al, 2005;Macleod et al, 2007;Matthiessen et al, 2006) and for long exposure times, the desorption phenomena are probably not negligible. In this case we have to investigate the elimination rates in further detail.…”
Section: Desorption Of Det Terbuthylazine and Isoproturon From Pocissupporting
confidence: 81%
“…However, the use of such equipment is often physically and logistically difficult, and it generates a large number of samples with a corresponding increase in analytical cost. For monitoring polar herbicides in freshwater, the use of polar organic chemical integrative samplers (POCIS) allows estimates of TWA concentrations (Alvarez et al, 2004;Alvarez et al, 2005). Nevertheless, the accuracy and the precision of these passive samplers for determining the ambient concentrations in rivers have not been fully demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the applications on the new passive samplers are concerned with comparison with spot sampling for quality assurance purposes [15,16,34]. Reviews on the applications of SPMDS to water monitoring have also been reported [11,12].…”
Section: Applications Of Passive Samplersmentioning
confidence: 99%
“…The PDMS rod on the other hand gives the TWA concentrations, thus giving lower detection limits. The POCIS sampler has been compared to standard watercolumn sampling for qualitative determination of organic contaminants associated with wastewater effluents entering New Jersey stream (USA) [34]. In another study, the POCIS was used to evaluate the level of contamination of headwaters by oestrogenic hormones from livestock farms in the U.K [35].…”
Section: Applications Of Passive Samplersmentioning
confidence: 99%
See 1 more Smart Citation